2024
DOI: 10.1038/s41428-023-00863-9
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging mechanochemistry for sustainable polymer degradation

Simay Aydonat,
Adrian H. Hergesell,
Claire L. Seitzinger
et al.

Abstract: Over 8 billion tons of plastic have been produced to date, and a 100% reclamation recycling strategy is not foreseeable. This review summarizes how the mechanochemistry of polymers may contribute to a sustainable polymer future by controlling the degradation not only of de novo developed designer polymers but also of plastics in existing waste streams. The historical development of polymer mechanochemistry is presented while highlighting current examples of mechanochemically induced polymer degradation. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 139 publications
0
5
0
Order By: Relevance
“…The kinetics of prolonged functionalization reactions under BMG conditions are likely to be competitive with those of chain scission, resulting in excessive backbone degradation and loss of desired bulk properties. 50 This degradation via BMG can be leveraged for polymer depolymerization, 26,51,52 chain-end functionalization, 53,54 or radical functionalization. 55 For PS, while chain scission under BMG is well documented above a limiting molar mass, Mlim (ca.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetics of prolonged functionalization reactions under BMG conditions are likely to be competitive with those of chain scission, resulting in excessive backbone degradation and loss of desired bulk properties. 50 This degradation via BMG can be leveraged for polymer depolymerization, 26,51,52 chain-end functionalization, 53,54 or radical functionalization. 55 For PS, while chain scission under BMG is well documented above a limiting molar mass, Mlim (ca.…”
Section: Introductionmentioning
confidence: 99%
“…One promising alternative is the depolymerization of polymers in the solid state via mechanically-induced reactions. Mechanochemical reactions are typically performed in ball mills, in which contacts and collisions between grinding surfaces (balls and reactor wall) supply the energy required to chemically transform the (usually particulate) solid reactants caught between these surfaces. , Mechanochemistry has been successfully demonstrated on a laboratory scale for the production of lignocellulosic biomass, , cellulose, ammonia and lignin. Particularly for poly­(ethylene terephthalate) (PET), Štrukil and Tricker et al recently demonstrated its complete depolymerization to monomers inside ball mills. Moreover, mechanochemical routes have recently been explored for the depolymerization of various polymers such as polystyrene (PS), , polyethylene (PE), and poly­(α-methylstyrene) (PMS) and in the dechlorination of polyvinyl chloride (PVC). , In addition to the ability to efficiently process solid reactants, ball milling is a highly scalable industrial process being utilized in a wide variety of grinding applications, from minerals and cement, to chemicals and pharmaceuticals. Despite these advantages, mechanochemical reactions are often seen and modeled as “black-boxes”, which hinders the fundamental understanding of mechanically induced reactions .…”
Section: Introductionmentioning
confidence: 99%
“…One promising alternative is the depolymerization of polymers in the solid state via mechanically-induced reactions. 14 16 Mechanochemical reactions are typically performed in ball mills, in which contacts and collisions between grinding surfaces (balls and reactor wall) supply the energy required to chemically transform the (usually particulate) solid reactants caught between these surfaces. 15 , 17 20 Mechanochemistry has been successfully demonstrated on a laboratory scale for the production of lignocellulosic biomass, 21 , 22 cellulose, 23 25 ammonia 26 29 and lignin.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetics of prolonged functionalization reactions under BMG conditions are likely to be competitive with those of chain scission, resulting in excessive backbone degradation and loss of desired bulk properties. 50 This degradation via BMG can be leveraged for polymer depolymerization, 26,51,52 chain-end functionalization, 53,54 or radical functionalization. 55 For PS , while chain scission under BMG is well documented above a limiting molar mass, M lim ( ca.…”
Section: Introductionmentioning
confidence: 99%